2020
DOI: 10.1017/s0954579420001467
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing competence among a high-risk sample of emerging adults: Prospective predictions and biological considerations

Abstract: Few conditions epitomize severe and chronic stress to a greater extent than child maltreatment, which can derail development across multiple domains of functioning and throughout the life course. Furthermore, child maltreatment tends to co-occur with other adversities, such as poverty. Many individuals grow up under the stressful conditions of these adversities and exhibit developmental competence. The current study prospectively charted the developmental progression of economically disadvantaged maltreated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 106 publications
3
7
0
Order By: Relevance
“…To our knowledge, this is the first study to delineate various profiles of resilience using a national probability sample of children in the child welfare system. Our findings corroborate past personcentered studies that found different patterns of resilience among individuals with a history of maltreatment (Martinez-Torteya et al, 2017;Russotti et al, 2020;Yates & Grey, 2012) and offer compelling evidence for the multifaceted nature of resilience.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…To our knowledge, this is the first study to delineate various profiles of resilience using a national probability sample of children in the child welfare system. Our findings corroborate past personcentered studies that found different patterns of resilience among individuals with a history of maltreatment (Martinez-Torteya et al, 2017;Russotti et al, 2020;Yates & Grey, 2012) and offer compelling evidence for the multifaceted nature of resilience.…”
Section: Discussionsupporting
confidence: 89%
“…The low cognitive resilience profile and the low emotional and behavioral resilience profile validate the notion that resilience is not an "all or nothing" phenomenon (Luthar, 2013) in that children with these profiles displayed more resilience in certain areas while showing less resilience in other areas. The low cognitive resilience profile appears to align with school maladaptation profiles identified in prior research (e.g., "school maladaptation/family protection profile" in Martinez-Torteya et al, 2017; "work/school impairment" profile in Russotti et al, 2020). However, the low cognitive resilience profile identified in the current study is unique in that it was based on specific measures of language/cognitive development and pinpoint a group with less resilience in language development, whereas the school maladaptation profiles in previous studies encompassed broader indicators of school adaptation (e.g., educational attainment, employment status, peer relations) beyond language/cognitive ability.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Latent profile analysis (LPA) enables the identification of such hidden profiles, and, moreover, can handle missing data and offers model fit statistics (Lanza & Cooper, 2016). Hence, LPA addresses the notion of resilience that adaptation in one domain of functioning only gains meaning in relation to the individual's functioning in other domains (Luthar, 2006;Russotti, Warmingham, Handley, Rogosch, & Cicchetti, 2020). In the current person-centered study, we aimed to identify profiles of resilience in emerging adulthood and to examine how these profiles are related to multiple parenting behaviors and personality traits assessed in adolescence.…”
Section: Predictions From Parenting and Personality In Adolescencementioning
confidence: 99%
“…Latent profile analysis (LPA) enables the identification of such hidden profiles, and, moreover, can handle missing data and offers model fit statistics (Lanza & Cooper, 2016). Hence, person-centered approaches such as LPA provide a useful statistical method for addressing the claim that, in studying resilience, adaptation in one domain of functioning only gains meaning in relation to the individual's functioning in other domains (Infurna & Luthar, 2018;Russotti et al, 2020).…”
mentioning
confidence: 99%